Kepemimpinan dan Etika dalam Administrasi Publik: Menavigasi Tantangan Kepemimpinan di Era Kontemporer - Rindawati, Septi; Putri, Sudriyanti; Asnilan, Asnilan; Aprianita, Aprianita (SENGKUNI Journal (Social Science and Humanities Studies), 2022)
Leadership and ethics play a crucial role in public administration, especially in the contemporary era of complex and diverse challenges. This article outlines the key role of leadership in addressing the various issues faced by the public sector, including difficult decision-making, management of limited resources, and increasingly complex public services. In addition, strong ethics in leadership are key to maintaining public trust and ensuring transparency in public administration. As such, this article attempts to detail how effective and ethical leadership can help leaders in the public sector navigate the ever-evolving challenges of this contemporary era.